Governance, Accountability, and Accounting Practices in Village-Owned Enterprises (Bumdes): A Scoping Review - Ismail, Susanty; Amaliah, Tri Handayani; Mahdalena, Mahdalena (Journal Research of Social Science, Economics, and Management, 2026)
The management of Village-Owned Enterprises (BUMDes) in Indonesia has become a strategic focus within national rural development policy, particularly since the enactment of Law No. 6 of 2014 concerning Villages, which emphasizes village autonomy and economic self-sufficiency. Despite this policy support, many BUMDes continue to face significant challenges in governance, accountability, and the implementation of sound accounting practices.  This research aims to map and synthesize academic literature regarding governance, accountability, and accounting practices in Village-Owned Enterprises (BUMDes). The study used a scoping review approach  with reference to the five-stage methodological framework of Arksey and O'Malley (2005). The literature search was carried out through the Scopus database using an advanced search strategy on journal articles published in the 2014–2024 period. From the selection process, 25 articles were obtained that were analyzed in depth. The mapping results show that the discourse on BUMDes is dominated by the theme of hybrid organizational tensions, political attachment in governance, and the gap between expectations and the reality of accountability. Meanwhile, studies that highlight the technical aspects of the implementation of accounting standards and long-term (longitudinal) performance evaluation are still relatively limited. The implications of this study confirm the importance of developing a more integrative and contextual approach to village accounting to bridge social and economic missions. The novelty of this research lies in the presentation of a thematic map of the Scopus-based literature that explicitly synthesizes the intersection between governance, accountability, and accounting practices in a single analytical framework.